Steindler flexorplasty to restore elbow flexion in C5-C6-C7 brachial plexus palsy type - Monreal, Ricardo (Journal of Brachial Plexus and Peripheral Nerve Injury, 2007)
Background Loss of elbow flexion due to traumatic palsy of the brachial plexus represents a major functional handicap.Then, the first goal in the treatment of the flail arm is to restore the elbow flexion by primary direct nerve surgery or secondary reconstructive surgery.There are various methods to restore elbow flexion which are well documented in the medical literature but the most known and used is Steindler flexorplasty.This review is intended to detail the author’s experience with Steindler flexorplasty to restore elbow flexion in patients with brachial plexus palsy C5-C6-C7 where wrist extensors are paralyzed or weakened.Methods We conducted a retrospective follow-up study of 12 patients with absent or extremely weak elbow flexion (motor grade 2 or less), wrist/finger extensor and triceps palsy associated; who had undergone surgical reconstruction of the flail upper limb by tendon transfer (Steindler flexorplasty) and wrist arthrodesis to restore elbow flexion. The aetiology of elbow weakness was in all patients brachial plexus palsy (C5-C6-C7 deficit). Data were collected from medical records and from the information obtained during follow-up visits.Age, sex, preoperative strength (rated on a 0 to 5 scale for the flexors of the elbow, wrist flexors, pronator and triceps), previous surgery, length of follow-up, other associated operative procedures, results and complications were recorded.Results The results are the follows: Eleven patients were found to have very good or good function of the transferred muscles. One patient had mild active flexion of the elbow despite the reconstructive procedure.There were no major intraoperative complications. Two patients experienced transient, intermittent nocturnal ulnar paresthesias postoperatively. In both patients these symptoms subsided without further surgery.Conclusion Our study suggests that in patients with C5-C6-C7 palsy where the wrist and finger extensors are paralyzed or weaked, the flexor-pronators muscles of the forearm are strong but the triceps is not available for transfer; Steindler flexorplasty to restore elbow flexion should be complemented with wrist arthrodesis.